Control and stabilization of the modal content of fiber amplifiers using traveling waves - Jauregui, Cesar; Stihler, Christoph; Kholaif, Sobhy; Tu, Yiming; Limpert, Jens (Optics Express, 2021)
In this work we present a novel way to manipulate the effect of transverse mode instability by inducing traveling waves in a high-power fiber system. What sets this technique apart is the fact that it allows controlling the direction of the modal energy flow, for the first time to the best of our knowledge. Thus, using the method proposed in this work it will be possible to transfer energy from the higher-order mode into the fundamental mode of the fiber, which mitigates the effect of transverse mode instability, but also to transfer energy from the fundamental mode into the higher-order mode. Our simulations indicate that this approach will work both below and above the threshold of transverse mode instability. In fact, our model reveals that it can be used to force a nearly pure fundamental mode output in the fiber laser system almost independently of the input coupling conditions. In this context, this technique represents the first attempt to exploit the physics behind the effect of transverse mode instability to increase the performance of fiber laser systems.
CRIS-Team Scopus Importer:2023-04-20